2017
DOI: 10.4108/eai.31-5-2017.152558
|View full text |Cite
|
Sign up to set email alerts
|

Large-Signal Analysis and Characterization of a RF SOI-based Tunable Notch Antenna for LTE in TV White Space Frequency Spectrum

Abstract: The demand for spectrum resources has increased dramatically with the explosion of wireless mobile devices and services. The Cognitive Radio (CR) associated with TV white space frequencies defined between 470 MHz to 790 MHz is one solution to excel the spectrum resources shortage and address LTE low bands. The antenna design to cover such a wide band is a twofold challenge. First Electromagnetic fundamental limits impose a tradeoff between antenna efficiency, miniaturization and its frequency band wideness, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…For extreme miniaturization (planar notch antenna in λ/26 at 635 MHz with 600-960 MHz tuning range), the second category aims to distribute the constraints between ESA and a DTC in a co-design [4] [7]. It is shown that the tunable ESA radiation efficiency is equally affected by the finite conductivity of the antenna and the TC RF losses.…”
Section: Introductionmentioning
confidence: 99%
“…For extreme miniaturization (planar notch antenna in λ/26 at 635 MHz with 600-960 MHz tuning range), the second category aims to distribute the constraints between ESA and a DTC in a co-design [4] [7]. It is shown that the tunable ESA radiation efficiency is equally affected by the finite conductivity of the antenna and the TC RF losses.…”
Section: Introductionmentioning
confidence: 99%